ELUCIDATION OF NATIONAL-CULTURAL CHARACTERISTICS OF THE SEMANTIC GROUPING OF APHORISMS IN ENGLISH AND UZBEK FROM A LINGUISTIC-COMPARATIVE POINT OF VIEW THROUGH THE WORKS OF THE GREAT POET AND THINKER ALISHER NAVOI - Khakimova Mastura Fayzillayevna (Western European Studies, 2024)
In this article, aphorisms and their place in the literary process, their translations in foreign languages are shown through the aphorisms in the works of Alisher Navoi, and special attention is paid to the traditions of translation
Keywords: semantic; aphorisms; linguistic-comparative; philosophy